THE APPLICATION OF MNEMONICS METHODS IN TEACHING PHONOLOGY - Марина С. Јањић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2015)
The paper deals with issues related to teaching methodology in the processing of materials based on the facts that must be remembered. The need for storing classifications of sounds according to various criteria in long-term memory (particularly the division of consonant voicing, manner and place of creation) is not only a problem for students, but seem to be a regressive factor in the processing of important units in the field of morfophonology, in the first place voice alternation. The paper starts from the premise that, despite the criticisms that are directed at the expense of dogmatic and reproductive classes, there are many values of the traditional school which, if used in the right way conforming to the spirit of constructivist teaching, can be very effectively applied even in the modern school. One of them is the method of mnemonics, which represents the most creative way of reproductive learning. This paper analyzes the possibilities of its application in a modern approach to teaching phonology with the creation of innovative pedagogical applications.